Genética do florescimento e do ciclo reprodutivo do feijoeiro - Rosa, Daniele Piano (2013)
There are two early-maturing common bean cultivars registered for cultivation in the Rio Grande do Sul State. Thus, there is demand for cultivars for early harvest to improve the management of crop fields, ensure the best selling price to producer and, also, allow the second season harvest before the frost period. Thus, the aims of this research were to study the genetic of the flowering, reproductive period and cycle in common bean. For this, were obtained the F1 and F2 generations to Iraí x BRS Esplendor and Iraí x IPR Tangará hybrid combinations. The parents and the F1 and F2 generations were sown in the field and, evaluated for flowering, reproductive period and cycle. The flowering showed broad sense heritability estimates of intermediate (h2a: 44.87%) to high (h2a: 61.38%) magnitude and the highest selection gains. The reproductive period showed broad sense heritability estimates ranging from low (h2a: 22.94%) to intermediate (h2a: 59.20%) values and, selection gains lower than those obtained with the flowering. To the character cycle were obtained broad sense heritability estimates of intermediate (h2a: 45.38%) to high (h2a: 62.93%) magnitude and, selection gains intermediate to those obtained to flowering and to reproductive period. Thus, the flowering is the character more efficient to the selection of common bean lines of the early cycle.